NAP: Research and Development of a Peptide Derived from Activity‐Dependent Neuroprotective Protein (ADNP) - Gozes, Illana (CNS Drug Rev, 2006)
Activity‐dependent neuroprotective protein (ADNP) is essential for brain formation. Peptide activity scanning identified NAP (NAPVSIPQ) as a small active fragment of ADNP that provides neuroprotection at very low concentrations. In cell culture, NAP has demonstrated protection against toxicity associated with the beta‐amyloid peptide, N‐methyl‐D‐aspartate, electrical blockade, the envelope protein of the AIDS virus, dopamine, H(2)O(2), nutrient starvation and zinc overload. NAP has also provided neuroprotection in animal models of apolipoprotein E deficiency, cholinergic toxicity, closed head injury, stroke, middle aged anxiety and cognitive dysfunction. NAP binds to tubulin and facilitates microtubule assembly leading to enhanced cellular survival that is associated with fundamental cytoskeletal elements. A liquid‐chromatography, mass spectrometry assay demonstrated that NAP reaches the brain after either intravenous or intranasal administration. In a battery of toxicological tests including repeated dose toxicity in rats and dogs, cardiopulmonary tests in dogs, and functional behavioral assays in rats, no adverse side effects were observed with NAP concentrations that were ˜500‐fold higher than the biologically active dose. A Phase Ia clinical trial in the US assessed the tolerability and pharmacokinetics of intranasal administration of NAP in sequential ascending doses. The results supported the safety and tolerability of a single dose of NAP administered at up to 15 mg intranasally. Furthermore, dosing was recently completed for a second Phase I clinical trial in healthy adults and elderly volunteers with an intravenous formulation of NAP. NAP is poised for further clinical development targeting several indications, including Alzheimer's disease.